Proteoform Analysis of Matrix Metalloproteinase-9/Gelatinase B and Discovery of Its Citrullination in Rheumatoid Arthritis Synovial Fluids - Grillet, Bernard; Yu, Karen; Ugarte-Berzal, Estefania; Janssens, Rik; Pereira, Rafaela Vaz Sousa; Boon, Lise; Martens, Erik; Berghmans, Nele; Ronsse, Isabelle; Van Aelst, Ilse; Fiten, Pierre; Conings, René; et al. (Frontiers in Immunology, 2021)
Objectives: To explore posttranslational modifications (PTMs), including proteolytic activation, multimerization, complex formation and citrullination of gelatinases, in particular of gelatinase B/MMP-9, and to detect in gelatin-Sepharose affinity-purified synovial fluids, the presence of specific MMP proteoforms in relation to arthritis. Methods: Latent, activated, complexed and truncated gelatinase-A/MMP-2 and gelatinase B/MMP-9 proteoforms were detected with the use of zymography analysis to compare specific levels, with substrate conversion assays, to test net proteolytic activities and by Western blot analysis to decipher truncation variants. Citrullination was detected with enhanced sensitivity, by the use of a new monoclonal antibody against modified citrullines. Results: All MMP-9 and MMP-2 proteoforms were identified in archival synovial fluids with the use of zymography analysis and the levels of MMP-9 versus MMP-2 were studied in various arthritic diseases, including rheumatoid arthritis (RA). Secondly, we resolved misinterpretations of MMP-9 levels versus proteolytic activities. Thirdly, a citrullinated, truncated proteoform of MMP-9 was discovered in archival RA synovial fluid samples and its presence was corroborated as citrullinated hemopexin-less MMP-9 in a small prospective RA sample cohort. Conclusion: Synovial fluids from rheumatoid arthritis contain high levels of MMP-9, including its truncated and citrullinated proteoform. The combination of MMP-9 as analyte and its PTM by citrullination could be of clinical interest, especially in the field of arthritic diseases.